Next-Generation Sequencing of Cerebrospinal Fluid for the Diagnosis of Neurocysticercosis - Fan, Siyuan; Qiao, Xiaodong; Liu, Lei; Wu, Honglong; Zhou, Jiali; Sun, Ruixue; Chen, Qing; Huang, Yan; Mao, Chenhui; Yuan, Jing; Lu, Qiang; Ge, Ying; et al. (Frontiers in Neurology, 2018)
Backgrounds: Neurocysticercosis (NCC) is the most common helminthic infection of the central nervous system (CNS). The diagnosis of NCC is sometimes challenging due to its heterogenous clinical manifestations and the variable sensitivity and specificity of neuroimaging and serological tests. Methods: Next-generation sequencing (NGS) of cerebrospinal fluid (CSF) was used to detect pathogens in patients with clinically suspected CNS infections. A series of patients diagnosed with NCC is reviewed here. Results: Using NGS of CSF, four patients were diagnosed with NCC. The reads corresponding to Taenia solium ranged from 478 to 117,362, with genomic coverage of 0.0564-11.15%. Reads corresponding to T. solium were not found in non-template controls and far exceeded those of the background microorganisms in patients with NCC, facilitating the interpretation of the NGS results. Conclusions: This case series demonstrates that NGS of CSF is promising in the diagnosis of NCC in difficult to diagnose cases. Larger studies are needed in the future.